Mathematical modeling of the acetabulum fracture (type 62-B1.3 by AO/ASIF) deformities and hip endoprosthetics in combination with osteosynthesis - Vyrva, Oleg; Vatamanitsa, Dmytro; Karpinsky, Mykhaylo; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Secondary degenerative disabling changes in the hip joint often develop in the long term after surgical treatment of hip fractures. A well-founded differential approach to the selection of endoprosthesis components and additional means of stabilizing bone fragments is necessary. Objective. To investigate changes in relative deformation values in a hip joint model with a acetabulum fractures 62–B1.3 type by AO/ASIF classification under the conditions of its endoprosthesis using various osteosynthesis options. Methods. A basic finite-element model of the pelvic girdle of a person with a fracture of the bottom of the cruciate ligament type 62-B1.3 (АО/ASIF) was developed, on which 7 variants of endoprosthesis of the left hip joint were modeled: without fracture (1); without osteosynthesis of fragments (2); fixation of a fragment of the acetabulum back wall with two screws (3), two screws and a bone plate (4), two screws and a bone plate with a Jumbo cup implantation (5); 5 case, long screw in the front column (6); option 5, long screws in the front and rear columns (7). Results. When using a large-sized Jumbo cup, the relative deformations of the bone regenerate in the center of the bottom of the KZ were reduced to 1.0 %, regardless of the osteosynthesis option. Around the free fragment of the short circuit, the largest relative deformations (3.0 %) were found in version 5 of the model. The use of long rods in the columns led to decrease in the relative deformations of the bone regenerate around the free fragment of the KZ to 2.0 %. Conclusions. Mathematical models proved that an increase in the number of osteosynthesis tools under the conditions of the total hip endoprosthesis replacement, 62-B1.3 (АО/ASIF) type KZ fracture leads to a decrease in the relative deformations of the bone regenerate along the entire fracture line. The use of a large-sized Jumbo cup makes it possible to reduce the level of relative deformations of the bone regenerate in the central part of the KZ.